Vocational Identity Reconstruction in Individuals with Spinal Cord Injury: A Narrative Approach - Kutsal, Ahmet; Özdemir, Mehmet (KMAN Counseling & Psychology Nexus, 2025)
This study aimed to explore how individuals with spinal cord injury reconstruct their vocational identities through personal narratives following their injury. This research employed a qualitative narrative methodology to examine the lived experiences of 22 participants with spinal cord injury residing in Turkey. Participants were selected through purposive sampling to ensure diversity in age, gender, and pre-injury occupational backgrounds. Data were collected through semi-structured interviews, which allowed participants to articulate their vocational journeys in detail. Interviews were conducted either face-to-face or via secure video conferencing, recorded with consent, and transcribed verbatim. Thematic narrative analysis was applied using NVivo software to identify recurring patterns, story arcs, and identity-related shifts across participants’ accounts. Data saturation was achieved at 22 participants, ensuring a comprehensive representation of shared and divergent experiences. Three overarching themes emerged from the analysis: disruption of pre-injury identity, navigating vocational transition, and reconstruction of vocational identity. Participants described initial experiences of emotional disorientation, loss of purpose, and altered self-perception. As they moved through recovery, they sought support systems, reevaluated career paths, engaged in skill development, and encountered motivational fluctuations. Reconstruction of vocational identity involved processes of acceptance, narrative meaning-making, and redefinition of success. Institutional and societal barriers, such as limited accessibility and workplace stigma, were significant obstacles, while family encouragement, personal resilience, and community engagement facilitated identity renewal. Vocational identity reconstruction following spinal cord injury is a complex, narrative-driven process shaped by emotional, social, and structural factors. Narrative-informed, person-centered vocational rehabilitation practices that emphasize meaning-making and identity support are essential for holistic recovery and reintegration.